Analysis of Methods for Intensifying Heat and Mass Transfer in Liquid Media - Anatoliy Pavlenko (Energies)
In many technological processes, liquids or mixtures of mutually insoluble liquids, suspensions, emulsions, etc., are used as working media. The transformation of the energy supplied to such media and the related effects can be usefully realised not only for the implementation of technological processes but also for their intensification. In this context, an important task in increasing the efficiency of the use of the supplied energy is the analysis of the processes that take place in liquids or their mixtures at the level of thermodynamic saturation. In this work, it is shown that the creation of thermodynamic conditions for local energy transformation in a disperse system significantly increases the intensity of heat and mass transfer processes, and in some technologies, e.g., homogenisation, dispersion can be increased by 2–3 times in comparison with traditional methods at the same energy consumption.